EFFECT OF SPECIAL EXERCISES ON DEVELOPING SOME PHYSICAL ABILITIES, INDICATORS, AND BIOCHEMICALS IN YOUNG BASKETBALL PLAYERS - Mohammad Kadhim Ashour; Nadia Mahdi Mohammed; Hussein Fakher Jassim (Proximus Journal Publishing, 2025)
The researchers aimed to prepare special exercises to develop some physical and biochemical abilities in young basketball players and to identify the effect of special exercises to develop some physical and biochemical abilities in young basketball players, the researchers used the experimental method to suit the nature of the study. The research community was determined from the young players of the Popular Mobilization Club in basketball, as the total research community reached (25) players for the sports season (2024 – 2025), as for the research sample that was chosen from the research community, it amounted to (20) players, and (20) players were chosen from among them to represent the research sample: (10) players for the experimental group and (10) players for the control group, the training curriculum also continued and was applied to the study sample for a period of (6 weeks), with three training units per week. The researchers used appropriate statistical methods through the Statistical Bag Program (SPSS), in the third chapter, the researchers presented, analyzed and discussed the results using their own tables. As for the most important conclusions, the results showed a clear development in physical abilities after applying special exercises to the members of the experimental group sample, the results showed that special exercises contributed to the development of the biochemical indicators under investigation, there is a significant difference between the pre- and post-test in physical ability tests and biochemical indicators in the experimental and control research sample. As for the recommendations, it is necessary to adopt special exercises as an essential part of training programs for athletes in various games, diversify special exercises to suit the nature of sports activity and the age group of players. Expanding studies in the future to include the psychological, physical and physiological aspects.
Keywords: Special Exercises; Physical Abilities; Biochemical Indicators